Environmental protection through the prism of enlargement: Time for reflection - Bogojevic, S; Drenovak-Ivanovic, M (Kluwer Law International, 2019)
In the wake of crises and “enlargement fatigue”, EU politics deprioritized enlargement. Recently, however, the Commission motioned a reinvigorated enlargement prospect for the Western Balkans, identifying Serbia and Montenegro as the front runners. This paper advises that in going forward, the EU should also look back at its five decades of enlargement. The article focuses on environmental protection – a key EU public policy – and the way in which it features in the ever-evolving accession conditions and accession acts. It emerges that environmental protection has been marginalized throughout EU’s enlargement history. Taking Serbia as a case study, it is shown that this is highly problematic, since environmental protection is linked to safeguarding the rule of law – an essential criterion for EU membership. The role of environmental protection in the EU’s enlargement policies should thus be reprioritized.